ELECTIONS IN CENTRAL ASIAN STATES: OLITICAL RIVALRY IN A TRANSITIONAL SOCIETY - BORISHPOLETS, Ksenia (CENTRAL ASIA AND THE CAUCASUS, 2006)
The beginning of the third millennium is a very difficult time to make an objective assessment of the events going on in the countries and regions of the world. The images of the Great Chess Board, the classical heritage postulates espoused by geopoliticians, the attempts to create new “symbols of evil,” and the deliberate criticism of democratic principles as a universal political dominant are too often distorting the objective picture of our reality. In this respect, a well-balanced analysis of the electoral processes in the newly independent states of Central Asia is of considerable interest. The significance of the party and personal composition of the power institutions in the region’s countries is determined not only by their resource potential, the situation in Afghanistan, and the fight to prevent new threats to international security. Although Central Asia is historically closely related to Russia, today there are several other major foreign political actors in the region who are declaring their interests: the U.S., Turkey, China, Iran, Pakistan, India, and the European Union with its individual countries. Their participation is giving all the political processes going on in the Central Asian republics a comprehensive and de facto global dimension. Acquiring national sovereignty and achieving development under conditions of post-union statehood have become serious tests for these countries. During these years, their social systems have come close to the critical mark on several occasions, while the crisis trends in the social and political spheres have not been fully overcome, despite the optimism instilled in the official statements. On the whole, the situation in the region refutes the apocalyptic forecasts regularly offered by some experts and politicians at the beginning of the 1990s, and is currently characterized by significant positive shifts. All the same, the development and stability prospects of the Central Asian states is still a topic of numerous discussions in which parliamentary and presidential elections have recently found themselves the center of attention.